2014
DOI: 10.1371/journal.pone.0087420
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Derived Proinflammatory Cytokines Induce Hypomyelination in the Periventricular White Matter in the Hypoxic Neonatal Brain

Abstract: Hypoxic exposure in the perinatal period causes periventricular white matter damage (PWMD), a condition associated with myelination abnormalities. Under hypoxic conditions, glial cells were activated and released a large number of inflammatory mediators in the PWM in neonatal brain, which may result in oligodendrocyte (OL) loss and axonal injury. This study aims to determine if astrocytes are activated and generate proinflammatory cytokines that may be coupled with the oligodendroglial loss and hypomyelination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 41 publications
3
46
0
Order By: Relevance
“…Astrocytes contribute to repair of the brain after insult; however, evidence is accumulating that reactive astrocytes mediate the pathophysiology of perinatal brain injury, potentially via the release of pro-inflammatory cytokines or hyaluronan [41][42][43] . We did not observe astrogliosis within the late-onset FGR brains; however, we have previously shown altered astrocyte morphology, without altered density, in late-onset FGR animals examined at term with altered astrocytic end-feet attachment at blood vessels, leading to altered cerebrovascular function [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes contribute to repair of the brain after insult; however, evidence is accumulating that reactive astrocytes mediate the pathophysiology of perinatal brain injury, potentially via the release of pro-inflammatory cytokines or hyaluronan [41][42][43] . We did not observe astrogliosis within the late-onset FGR brains; however, we have previously shown altered astrocyte morphology, without altered density, in late-onset FGR animals examined at term with altered astrocytic end-feet attachment at blood vessels, leading to altered cerebrovascular function [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Since tissue inflammation correlating with presence of the parasite and axonal damage was observed in infected mice as early as seven dpi [17], we primarily focused on detection of proinflammatory cytokines and nitric oxide. These factors are known to be produced by activated astrocytes and microglia and may contribute to pathological processes [2629]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that IL-1β decreases the proliferation and survival rates of neural precursor cells by activating IL-1β/IL-1R signaling and upregulating p53 and p53-mediated genes, which leads to cell cycle inhibition and Puma/Bax-mediated apoptosis in neural precursor cells (Guadagno et al , 2015). Moreover, increased IL-1β production by microglia and astrocytes is linked to upregulated expression of IL-1R on oligodendrocytes and increased apoptosis of oligodendrocytes in periventricular white matter of neonatal brain (Deng et al , 2014; Xie et al , 2016). Thus, IL-1β is detrimental to immature brain with neonatal HIE through inhibiting the proliferation and survival of brain cells, such as neurons and oligodendrocytes.…”
Section: Molecular Mediators Of Inflammation In Neonatal Hi Brain mentioning
confidence: 99%